DNA barcoding for identification of consumer-relevant mushrooms: A partial solution for product certification?. (1st January 2017) - Raja, Huzefa A.; Baker, Timothy R.; Little, Jason G.; Oberlies, Nicholas H.
Highlights: Thirty-three commercially used fungal samples were analyzed via ITS barcoding. Samples included: powdered mycelium, culinary mushrooms, dietary supplement capsules. We discuss the pros/cons of DNA barcoding for identification of such fungal samples. Abstract: One challenge in the dietary supplement industry is confirmation of species identity for processed raw materials, i.e. those modified by milling, drying, or extraction, which move through a multilevel supply chain before reaching the finished product. This is particularly difficult for samples containing fungal mycelia, where processing removes morphological characteristics, such that they do not present sufficient variation to differentiate species by traditional techniques. To address this issue, we have demonstrated the utility of DNA barcoding to verify the taxonomic identity of fungi found commonly in the food and dietary supplement industry; such data are critical for protecting consumer health, by assuring both safety and quality. By using DNA barcoding of nuclear ribosomal internal transcribed spacer (ITS) of the rRNA gene with fungal specific ITS primers, ITS barcodes were generated for 33 representative fungal samples, all of which could be used by consumers for food and/or dietary supplement purposes. In the majority of cases, we were able to sequence the ITS region from powdered mycelium samples, grocery store mushrooms, and capsules from commercial dietary supplements. After generating ITS barcodes utilizing standard procedures accepted by the Consortium for the Barcode of Life, we tested their utility by performing a BLAST search against authenticate published ITS sequences in GenBank. In some cases, we also downloaded published, homologous sequences of the ITS region of fungi inspected in this study and examined the phylogenetic relationships of barcoded fungal species in light of modern taxonomic and phylogenetic studies. We anticipate that these data will motivate discussions on DNA barcoding based species identification as applied to the verification/certification of mushroom-containing dietary supplements.